Role of Capsid anchor in the morphogenesis of Zika virus - Rana, J; Slon Campos, J; Leccese, G; Francolini, M; Bestagno, M; Poggianella, M; Burrone, O (American Society for Microbiology, 2018)
The flavivirus capsid protein (C) is separated from the downstream pre-membrane (PrM) protein by a hydrophobic sequence named capsid anchor (Ca). During polyprotein processing, Ca is sequentially cleaved by the viral NS2B/NS3 protease on the cytosolic side and by signal peptidase on the luminal side of the ER. To date, Ca is considered important mostly for directing translocation of PrM into the ER lumen. In this study, the role of Ca in the assembly and secretion of ZIKV was investigated using a pseudovirus-based approach. Our results show that, while Ca-mediated anchoring of C to the ER membrane is not needed for the production of infective particles, Ca expression in cis with respect to PrM is strictly required to allow proper assembly of infectious particles. Finally, we show that the presence of a heterologous, but not the homologous, Ca induces degradation of E through the autophagy/lysosomal pathway.IMPORTANCE The capsid anchor (Ca) is a single pass transmembrane domain at the C-terminus of the capsid protein (C) known to function as a signal for the translocation of PrM into the ER lumen. The objective of this study was to further understand the role of Ca in ZIKV life cycle, whether involved in the formation of nucleocapsid through association with C or in the formation of viral envelope. In this study, we show that Ca has a function beyond the one of translocation signal, controlling protein E stability and therefore its availability for assembly of infectious particles.